2010
DOI: 10.1002/anie.200907082
|View full text |Cite
|
Sign up to set email alerts
|

A Light‐Driven DNA Nanomachine for the Efficient Photoswitching of RNA Digestion

Abstract: Recently, DNA has gained attention as one of the most promising molecules for use in bottom-up nanotechnology. [1] In the last two decades, numerous DNA nanostructures with mechanical functions such as DNA tweezers, DNA walkers, and DNA gears have been constructed. [2,3] However, the practical use of DNA nanotechnology remains a great challenge. One of the problems limiting the application of DNA nanomachines is that oligo-DNAs or other small molecules have to be added as the "fuel" during each operation cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 37 publications
0
74
0
2
Order By: Relevance
“…[136a,193,207] Photoswitchable oligonucleotides have enabled precise reversible control of nucleic acid based processes such as DNA crosslinking [208] and DNA–RNA hybridization. [209] More complex photoswitching tools have also been reported, such as azobenzene-modified DNAzymes and ribozymes [210] to reversibly control RNA cleavage. Diarylethene photoswitches incorporated at the C5 position of uracil were installed in the T7 promoter region of a double-stranded DNA template, thereby allowing photo-switching of transcription.…”
Section: Optical Control Of Oligonucleotidesmentioning
confidence: 99%
“…[136a,193,207] Photoswitchable oligonucleotides have enabled precise reversible control of nucleic acid based processes such as DNA crosslinking [208] and DNA–RNA hybridization. [209] More complex photoswitching tools have also been reported, such as azobenzene-modified DNAzymes and ribozymes [210] to reversibly control RNA cleavage. Diarylethene photoswitches incorporated at the C5 position of uracil were installed in the T7 promoter region of a double-stranded DNA template, thereby allowing photo-switching of transcription.…”
Section: Optical Control Of Oligonucleotidesmentioning
confidence: 99%
“…Rationally designed DNA nanomachines can carry out a rotary motion by switching from B- to Z-DNA at high ionic strength (14), sense the pH (15,16) and respond to changes from visible to UV light (17). DNA ‘walkers’ are capable of directional movement based on strand displacement (18,19), enzymatic activity (20,21) or in accordance with the prescriptive DNA origami landscapes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto existing applications have shown that architecturally simpler DNA nanostructures like molecular tweezers (21) and beacons (22), DNAzymes (23,24) or DNA tetrahedrons (25) are suited for light-induced switching, but this has not yet been implemented for the switching of more complex origami-based DNA structures. By using a double-stranded DNA (dsDNA) rotaxane architecture (26) that we reversibly switched between a mobile and stalled macrocycle, we have recently shown that light-induced switching operations based on dimethylazobenzene (DMAB)-functionalized DNA sequences result in a more robust switching behavior than oligodeoxynucleotides (ODNs) functionalized with unmodified azobenzene (27), and thus may find broader applications in DNA nanotechnology.…”
Section: Introductionmentioning
confidence: 99%